Analisis Kinerja Keuangan Pemerintah Daerah Oku Selatan Tahun Anggaran 2013-2017 - Anis Feblin; Yulitiawati Yulitiawati (Jurnal Akuntansi dan Keuangan, 2020)
This study aims to determine the Financial Performance of the South OKU Local Government by using the Financial Ratio Analysis on the Regional Government Budget of the South OKU Regency in the fiscal year of 2013-2017. The type of research used in this research is descriptive research. The data that is processed is the Summary of Regional Government Budget for the Fiscal Year of 2013-2017, it is obtained from the Central Bureau of Statistics of South OKU Regency. The analysis used to analyze the Regional Financial Performance is by calculating the Independence Ratio, Growth Ratio, and Activity Ratio. Based on the results of calculations and analysis of Regional Financial Performance it can be concluded, that the Criteria for Rating the Independence Level can be said it is very Effective with an average ratio of 1,087.33%. South OKU Regency Government's Growth Rate is  ineffective with an average income growth ratio is 45.19%, total revenue growth is 11.53%, routine expenditure growth is 13.91% and development expenditure growth is 10.81%. Activity Ratios indicate imbalance on expenditure of the South OKU local government with an average routine expenditure growth ratio of 103.08% and development expenditure of 56.03%.